Pengaruh Kesehatan Mental Terhadap Efektivitas Pembelajaran Bahasa Arab Siswa - Muhammad Rivyal; Krisna Prananda; Ari Seven Nur Aripin; Yusuf Bachtiar; Dina Indriana; Wahyu Hidayat (Lembaga Pengembangan Kinerja Dosen, 2024)
This research is based on the fact that feelings of anxiety, sadness, low self-esteem, anger, and doubt are all factors that greatly influence the effectiveness of students' Arabic learning. Apart from that, students' behavior is also greatly influenced by their mood; some students have problems outside of school, such as in the family and community, so they are not motivated to study and learn more. The aim of this research is to determine how much influence mental health has on how well students learn Arabic. The research instrument was tested on 25 students, so the author took a sample of 100% of the population so that the sample size was 25 students. The research results showed that the correlation test obtained was 0.748 with a significance of 0.000. This means that there is a positive correlation between mental health and student learning effectiveness with a good relationship level because P < 0.05 (0.000 < 0.05). Meanwhile, the T test (Hypothesis) T count is 15,465 while the T table is 2,069, meaning 15,466 > 2,069, then H0 is rejected and Ha is accepted, meaning that there is an influence of mental health on the effectiveness of students' Arabic learning.